The Feasibility of a Web-Based Educational Lifestyle Program for People With Multiple Sclerosis: A Randomized Controlled Trial - Bevens, William; Weiland, Tracey J.; Gray, Kathleen; Neate, Sandra L.; Nag, Nupur; Simpson-Yap, Steve; Reece, Jeanette; Yu, Maggie; Jelinek, George A. (Frontiers in Public Health, 2022)
Background: Modifiable lifestyle factors are important to aid people with multiple sclerosis in the self-management of their disease. Current self-management programs are limited by their face-to-face mode of delivery but there is immense potential with the internet to deliver these programs effectively. Objective: The aims of this study are to assess the feasibility of a digitalised educational lifestyle self-management program for people with MS. Methods: In this randomised controlled trial, people with MS were randomly allocated to participate in a six-week tailored web-based educational lifestyle program or six-week generic standard-care educational course, and were blinded to their allocation. Participants were recruited through multiple sclerosis (MS) Societies in four countries: Australia, New Zealand, Canada, and the United States. The primary outcome was to assess acceptability of the program defined as percentage completion of all modules at six-weeks post-course commencement. Secondary outcomes included evaluating participant responses to the follow-up survey across three domains: accessibility, learnability, and desirability. Results: 35 participants from Australia, Canada, New Zealand, and the US completed the baseline survey and were randomised. Four participants were deemed ineligible due to incomplete baseline data; therefore, nine out of 15 and eight out of 16 participants completed 100% of the course in the intervention and standard-care arm courses, respectively. Conclusions: This study found that this web-based educational lifestyle program is a feasible means of delivering educational content to people with MS via the internet according to our a priori targets of >40% of participants in the intervention arm, and >25% in the control arm to completing 100% of the course. It is therefore appropriate to evaluate this intervention further in a large, randomised controlled trial.